Philip Karant: Roast Your Own (a Remedy for Bad Coffee) - Davidson, Alan E (Petits Propos Culinaires, 2024)
Philip Karant: Roast Your Own (a Remedy for Bad Coffee), Coffee Connoisseurs Inc. (Route 2, Box 59, Caryville, Tennessee 37714): 38 pages, large format paperback, comb-bound, some illustrations of old coffee roasters, etc., price on application (but evidently modest).